Education, work and social change young people and marginalization in post-industrial britain - Simmons, Robin; Thompson, Ron.; Russell, Lisa.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Drawing on a longitudinal study of the lives of NEET young people, this book looks beyond dominant discourses on youth unemployment to provide a rich, detailed account of young people's experiences of participation and non-participation on the margins of education and employment, highlighting the policy implications of this research.
Keywords: Science; Science; Science, general